Relationship between the hemoglobin-to-red cell distribution width ratio and post-stroke cognitive impairment: a prospective study - Liu, Yufeng; Xie, Zhe; Wang, Ping; Liu, Fan; Zhao, Liandong; Chen, Chun; Ge, Qiu; Wang, Mengchao; Zhi, Zhongwen (Frontiers in Aging Neuroscience, 2025)
BackgroundPost-stroke cognitive impairment (PSCI) is one of the main complications after stroke. The association between the hemoglobin-to-red cell distribution width ratio (HRR) and PSCI remains inadequately explored. Consequently, we performed a prospective study to assess whether HRR levels are associated with changes in cognitive function after acute ischemic stroke (AIS).MethodsA total of 296 AIS patients were recruited. HRR was measured within 24 h of admission, and cognitive function was assessed using the Mini-Mental State Examination (MMSE) one month post-onset. Logistic regression analysis was performed to identify independent risk and protective factors for the occurrence of PSCI. Restricted cubic splines (RCS) were used to explore the dose-response relationship between HRR and PSCI.Results129 of 296 participants (43.6%) developed cognitive impairment at 1 month. HRR in PSCI group was significantly lower than that in non-cognitive impairment group (P < 0.001). When HRR was taken as the categorical variable and with Q4 as the reference, the risk of PSCI in Q1 was the highest after adjusting multiple potential confounding factors (odds ratio [OR] = 2.702, 95% confidence interval [CI]= 1.222–5.977, P = 0.014). In addition, RCS curve exhibited that the relationship between HRR and PSCI was linear (P for nonlinear = 0.972, P for overall = 0.012). Subgroup analysis verified the stability of the results.ConclusionReduced HRR levels were linked to an increased risk of cognitive impairment, indicating that HRR may serve as a predictive factor for PSCI.